Epigenetic effects of stress and corticosteroids in the brain - Hunter, Richard G. (Frontiers in Cellular Neuroscience, 2012)
Stress is a common life event with potentially long lasting effects on health and behavior. Stress, and the corticosteroid hormones that mediate many of its effects, are well known for their ability to alter brain function and plasticity. While genetic susceptibility may influence the impact of stress on the brain, it does not provide us with a complete understanding of the capacity of stress to produce long lasting perturbations on the brain and behavior. The growing science of epigenetics, however, shows great promise of deepening our understanding of the persistent impacts of stress and corticosteroids on health and disease. Epigenetics, broadly defined, refers to influences on phenotype operating above the level of the genetic code itself. At the molecular level, epigenetic events belong to three major classes: DNA methylation, covalent histone modification and non-coding RNA. This review will examine the bi-directional interactions between stress and corticosteroids and epigenetic mechanisms in the brain and how the novel insights, gleaned from recent research in neuro-epigenetics, change our understanding of mammalian brain function and human disease states.